Identification and migration of primordial germ cells in Atlantic salmon, Salmo salar: characterization of vasa, dead end, and lymphocyte antigen 75 genes - Kazue Nagasawa; Jorge M.O. Fernandes; Yoshizaki, Goro; 吉崎, 悟朗; ヨシザキ, ゴロウ; Misako Miwa; Igor Babiak (Molecular Reproduction and Development, 2012)
No information exists on the identification of primordial germ cells (PGCs) in superorder Protacanthopterygii, which includes the Salmonidae family and Atlantic salmon (Salmo salar L.), one of the most commercially important aquatic animals worldwide. In order to identify salmon PGCs, we cloned the full-length cDNA of vasa, dead end (dnd), and lymphocyte antigen 75 (ly75/CD205) genes as germ cell marker candidates, and analyzed their expression patterns in both adult and embryonic stages of Atlantic salmon. Semi-quantitative RT-PCR results showed that salmon vasa and dnd were specifically expressed in testis and ovary, and vasa, dnd, and ly75 mRNA were maternally deposited in the egg. Vasa mRNA was consistently detected throughout embryogenesis, while dnd and ly75 mRNA were gradually degraded during cleavages. Further in situ hybridization (ISH) analyses revealed the localization of vasa, dnd mRNA, and Ly75 protein in PGCs of hatched larvae. Whole-mount ISH (WISH) detected vasa mRNA during embryogenesis, showing a distribution pattern somewhat different to that of zebrafish; specifically, at mid-blastula stage, vasa-expressing cells were randomly distributed at the central part of blastodisc, and then they migrated to the presumptive region of embryonic shield. Therefore, the typical vasa localization pattern of four clusters during blastulation, as found in zebrafish, was not present in Atlantic salmon. In addition, salmon PGCs could be specifically labeled with a green fluorescence protein (GFP) using Gfp-rt-vasa 3’UTR RNA microinjection for further applications. These findings may assist in understanding PGC development not only in Atlantic salmon but also in other salmonids. 25114005 journal article